Risk Management in Retail Supermarkets -‘DMart’ - Damani, Manjri (2008)
Globally, risk management has become an important ingredient of a smooth and successful running or a business. The benefits of risk management are beyond just avoiding losses. It seen as a tool of competitive advantage and enhanced reputation. In the mature markets, risk management in today's age is embedded into the business practice and functioning of the organisation. Every business has a risk management framework unique to its organization as the risks faced by every business are unique. The first part of the project is a literature review of the risk management and its scenario globally. However, there was not much literature work written exactly this topic. Therefore, I have made my concentration on the selective references which were exactly relevant. The risk management in supermarkets globally is then touched upon. It is true that these companies do have risk management systems in place, however they are not well documented. The case of Tesco plc is touched upon in greater detail. The scenario of retail in India is then looked upon which is contrasting to the well-developed structures abroad. Having said that, the retail scenario in India is at a very interesting stage due to the large opportunity of growth available in the sector. The case of DMart, a modern format discount store is taken into a detailed review. A form of an ethnographic research was done to propose a risk management tool into the systems of the company. Overall, there is a large scope of efficiency from the current levels with the incorporation of risk management into the system.